Territorial and environmental planning of Arcos (MG) in Landscape Units - Faria, Erick de Oliveira; Padoan, Lucas de Lima Fernandes (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Planning around environmental policies are important for the activities to deem sustainably. Studies on the landscape units, is becoming more popular in academia because it is a study that takes into account important environmental variables for a better characterization of the study area. This type of study also serves as a support for efficient management in order to get a better use of the potential of each landscape unit. This work then sought to identify and characterize the geographical area of the township of Arcos, based on the integration and interaction of biophysical components of ecosystems and their potential and multiple limitations for planning sustainable development.